2014
DOI: 10.3389/fnhum.2014.00005
|View full text |Cite
|
Sign up to set email alerts
|

Multiple neural states of representation in short-term memory? It’s a matter of attention

Abstract: Short-term memory (STM) refers to the capacity-limited retention of information over a brief period of time, and working memory (WM) refers to the manipulation and use of that information to guide behavior. In recent years it has become apparent that STM and WM interact and overlap with other cognitive processes, including attention (the selection of a subset of information for further processing) and long-term memory (LTM—the encoding and retention of an effectively unlimited amount of information for a much … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
147
1
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(162 citation statements)
references
References 99 publications
(205 reference statements)
13
147
1
1
Order By: Relevance
“…In other words, whether a noncued item is maintained or not may be a separate decision than whether it is attended or not. Such a dissociation is consistent with several models promoting a distinction between memory items that are in the current focus ("template") and other VWM representations that are held prospectively, or "on reserve" (LaRocque, Lewis-Peacock, Drysdale, Oberauer, & Postle, 2013;LaRocque, Lewis-Peacock, & Postle, 2014;Oberauer, 2002;Olivers, Peters, Houtkamp, & Roelfsema, 2011;Rerko & Oberauer, 2013;van Moorselaar, Olivers, et al, 2014;van Moorselaar, Theeuwes, & Olivers, 2014;Zokaei, Manohar, Husain, & Feredoes, 2014). These two types of VWM representations may have different mechanisms of maintenance, which operate more or less independently: (1) Task-relevant (here cued) representations are carried into a prioritized template status (which may also prioritize them for retrieval) regardless of the cue reliability, since there is little to lose by doing so.…”
Section: Discussionsupporting
confidence: 86%
“…In other words, whether a noncued item is maintained or not may be a separate decision than whether it is attended or not. Such a dissociation is consistent with several models promoting a distinction between memory items that are in the current focus ("template") and other VWM representations that are held prospectively, or "on reserve" (LaRocque, Lewis-Peacock, Drysdale, Oberauer, & Postle, 2013;LaRocque, Lewis-Peacock, & Postle, 2014;Oberauer, 2002;Olivers, Peters, Houtkamp, & Roelfsema, 2011;Rerko & Oberauer, 2013;van Moorselaar, Olivers, et al, 2014;van Moorselaar, Theeuwes, & Olivers, 2014;Zokaei, Manohar, Husain, & Feredoes, 2014). These two types of VWM representations may have different mechanisms of maintenance, which operate more or less independently: (1) Task-relevant (here cued) representations are carried into a prioritized template status (which may also prioritize them for retrieval) regardless of the cue reliability, since there is little to lose by doing so.…”
Section: Discussionsupporting
confidence: 86%
“…Although a number of state-based models of VWM have posited different activation states of representations that are established by the deployment of attention (LaRocque, Lewis-Peacock, & Postle, 2014), these models differ in their conceptualizations of how many items or elements can be selected. It has been proposed that only one item can be in the focus of attention (Oberauer, 2002;Olivers et al, 2011), thereby ensuring heightened processing efficiency for the selected information (Oberauer & Bialkova, 2009).…”
Section: How Many Representations In Vwm Can Be Selected?mentioning
confidence: 99%
“…Based on such observations, Drew et al (2011) suggested that these components do not exclusively reflect working memory storage, but also the allocation of focal attention to new target locations. When considered together, the hypothesis that CDA is not exclusively associated with storage but also with spatial attention, and the proposal that spatial attention results in a transient increase in the activation level of a subset of items that are currently held in working memory (e.g., Lewis-Peacock et al, 2012;LaRocque et al, 2014), suggest an alternative to the received storage interpretation of the CDA. Instead of reflecting the sustained maintenance of all visual items that are currently stored, this component may be associated with a relative transient activation of a subset of these items that were entered into working memory during the most recent encoding episode.…”
Section: Introductionmentioning
confidence: 99%